Concept of inculcating the culture of occupational safety among future qualified construction workers - Kulalaieva, N. (Problems of Engineer-Pedagogical Education, 2019)
The topicality of the research is explained by the need to procure the human and organizational security factors in the process of training future construction workers. The use of modern construction equipment and an increased responsibility for the quality of technological processes require the following. The purpose of the research is to substantiate and develop an effective concept of inculcating the culture of occupational safety among future qualified construction workers. The purpose of that is to develop their value attitude towards life and health, towards the environment, national dignity and self-awareness; to help them acquire systematized knowledge and skills necessary for building strategies for safe occupational conduct, identifying and using professionally relevant qualities that are important while organizing their own professional activity on the basis of their work-safety consciousness. Results. The paper provides normative legal international and state documents, which are based on the concept developed by the author, and which aim at ensuring education in the interests of sustainable development, in particular labor safety, health protection, energy efficiency and ecological safety, in the process of vocational training of future qualified construction workers. The suggested model of the development of occupational safety culture of future qualified construction workers illustrates its components, such as: acquisition of theoretical and practical knowledge in the field of occupational safety culture; development of professionally relevant skills on the basis of occupational safety awareness; development of professionally significant qualities important for its acquisition; their desire to acquire the culture of occupational safety and value attitude to professional activities. The content of the culture of occupational safety, which is highlighted in the paper, and its main requirements, as well as the pedagogical conditions for its development in the institutions of professional (vocational) education, will contribute to the implementation of the components of occupational safety awareness into the content of vocational training of future qualified construction workers.